2008
DOI: 10.1097/gme.0b013e3181405b74
|View full text |Cite
|
Sign up to set email alerts
|

Effect of human placental extract on menopausal symptoms, fatigue, and risk factors for cardiovascular disease in middle-aged Korean women

Abstract: Menopausal symptoms and fatigue in middle-aged Korean women improved after 8 weeks of HPE treatment, whereas risk factors for cardiovascular disease did not change during the study period.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
44
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(49 citation statements)
references
References 33 publications
3
44
0
1
Order By: Relevance
“…In concordance to Kong et al, who did not find any changes in risk factors for cardiovascular disease in elderly subjects after HPE course (Kong et al, 2008;Kong et al, 2012), we observed objectively registered improvements in parameters of exercise tolerance and lipid metabolism.…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…In concordance to Kong et al, who did not find any changes in risk factors for cardiovascular disease in elderly subjects after HPE course (Kong et al, 2008;Kong et al, 2012), we observed objectively registered improvements in parameters of exercise tolerance and lipid metabolism.…”
Section: Discussionsupporting
confidence: 76%
“…To our knowledge, there are 2 clinical trials reporting positive consequences of short-term application of HPE in subjects with fatigue (Kong et al, 2008;Larun et al, 2016). But in both studies fatigue was not verified as CFS, improvement of fatigue was checked by self-reports scaling adapted to Koreans, and HPE were used non-systemic -by subcutaneous abdominal injections (Kong et al, 2008) or as solutions per os every day (Kuratsune et al, 1994).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…No changes in risk factors for cardiovascular disease were observed in either groups. Menopausal symptoms and fatigue in middle-aged Korean women improved after 8 weeks of HPE treatment, whereas risk factors for cardiovascular disease did not change during the study period [45] .…”
Section: Discussionmentioning
confidence: 99%
“…Placental extract has long been used as a cosmetic supplement for skin care and skin pigmentation (Pal et al, 2002). Recently it has been reported that menopausal symptoms and fatigue in middle-aged women improved after the treatment with the aqueous placental extract (Kong et al, 2008). It has been reported that an aqueous extract of human placenta was found to offer protection against established experimental visceral leishmaniasis in BALB/c mice and hamsters, whether the Leishmania donovani strain involved was one that was sensitive or resistant to pentavalent antimony.…”
Section: Multiple Therapeutic Properties Of Aqueous Extract Of Human mentioning
confidence: 99%